Is Serbian Economy Ready to Use Digital Tools in Business Decision-Making Process - Barjaktarović, Lidija; Lazarevic, Biljana; Davidovic, Veljko (Industrija, 2019)
The aim of this article is to emphasize the importance of reactive to proactive approach in further simulation development and appliance, in order to increase the level of financial literacy. The subject of this paper is to get the opinion of Serbian employees, managers and owners of companies on the use of digital simulation Coin & Fund in companies’ business. The conducted research in 2019, on the basis of the questionnaire completed by 207 respondents out of 1,410 respondents (14.68% respondent rate) who received the questionnaire, confirmed that Serbian economy is ready to use digital tools in the lifelong learning process and business decision-making process. Respondents evaluated that Coin & Fund is extremely useful and supportive tool which helps in acquiring financial knowledge. Furthermore, it is extremely useful for understanding connection between made decisions and achieved financial result. Finally, the simulation represents company’s real business in an adequate way. It is important to stress the observations connected to the credible and reputable Coin & Fund team, and good cooperation between economy and academia.